Cohabiting Plant‐Wearable Sensor In Situ Monitors Water Transport in Plant. Issue 10 (9th March 2021) - Chai, Yangfan; Chen, Chuyi; Luo, Xuan; Zhan, Shijie; Kim, Jongmin; Luo, Jikui; Wang, Xiaozhi; Hu, Zhongyuan; Ying, Yibin; Liu, Xiangjiang
Abstract: The boom of plant phenotype highlights the need to measure the physiological characteristics of an individual plant. However, continuous real‐time monitoring of a plant's internal physiological status remains challenging using traditional silicon‐based sensor technology, due to the fundamental mismatch between rigid sensors and soft and curved plant surfaces. Here, the first flexible electronic sensing device is reported that can harmlessly cohabitate with the plant and continuously monitor its stem sap flow, a critical plant physiological characteristic for analyzing plant health, water consumption, and nutrient distribution. Due to a special design and the materials chosen, the realized plant‐wearable sensor is thin, soft, lightweight, air/water/light‐permeable, and shows excellent biocompatibility, therefore enabling the sap flow detection in a continuous and non‐destructive manner. The sensor can serve as a noninvasive, high‐throughput, low‐cost toolbox, and holds excellent potentials in phenotyping. Furthermore, the real‐time investigation on stem flow insides watermelon reveals a previously unknown day/night shift pattern of water allocation between fruit and its adjacent branch, which has not been reported before. Abstract : A plant‐wearable sensor in situ reveals water transport inside a plant. Due to a special design and the materials chosen, the realized plant‐wearable sensor is thin, soft, lightweight, air/water/light‐permeable, and shows excellent biocompatibility, therefore enabling detection in a continuous and non‐destructive manner.